A LITERATURE REVIEW ON TIRE COMPONENT REQUIREMENTS (Perner's Contacts, 2021)
This paper is a literature review about tire component requirements for innovation in tire construction. Herein are pointed out essential aspects expected in Tires’ structures from the mechanical point of view for future development of a realistic model for advanced simulation of tires (in miscellaneous operating conditions) and innovation in tire mechanics. Being composite structures, tires are made of many elements chosen with delicacy due to their intrinsic physical properties in regards to load effects. Since tires' mechanical behavior is directly linked to the parameters of its constituents (carcass, steel cord belt, and textile cord belt, namely), it is thereof imperative to grasp some solid pieces of knowledge about. Wherefore, the current contribution explored the mechanical requirements to be taken into account in the matrix (rubber) and reinforcements (steel cords and textile cords) for determining the inputs enabling to build up an accurate and simple computer model for improving tires simulation.